Simbol spiritualitas dan pandangan ekologis mantra ngalaksa dalam perspektif kajian ekolinguistik kultural - Rohmawati, Ai; Permadi, Tedi (Universitas Mulawarman, 2025)
This research aims to reveal the spiritual symbolism and ecological views in “Ngalaksa” mantram as an oral tradition of the Sundanese community in Rancakalong, Sumedang. Using a qualitative approach with a case study design and focused ethnographic analysis, this study examines the linguistic structure, symbolic meanings, and ecological functions of teks mantra used in various ritual stages such as “Jampé Nutu, Jampé Nginebkeun, Jampé Ngukus, and Jampé Ngibing.” The results show that each jampé functions as a prayer and a medium for spiritual communication as well as an ecological text containing environmental ethics and local wisdom values. Lexical elements such as menyan putih, talaga suci, bayu, bumi, and rasa reflect the ecological awareness of the Sundanese agrarian society who view nature as a living and sacred entity. “Ngalaksa” mantram also plays a role in maintaining cosmic balance, strengthening cultural identity, and becoming a medium for transmitting spiritual and ecological values across generations.